Regulation and Compliance in Telemedicine: Viewpoint - Julia Ivanova; Mollie R Cummins; Triton Ong; Hiral Soni; Janelle Barrera; Hattie Wilczewski; Brandon Welch; Brian Bunnell (Journal of Medical Internet Research)
The US COVID-19 Public Health Emergency ended on May 11, 2023. Lawmakers and regulators extended some flexibilities while they deliberate effective long-term telemedicine policy. Here, we discuss critical challenges in telemedicine compliance and regulation grounded in scholarly literature and current events. We specifically consider obstacles and progress toward solutions in telemedicine law and regulation regarding privacy and security issues, care across state borders, and prescribing over telemedicine in the United States. We conclude that simplified policies are needed to keep telemedicine accessible to providers and patients and that current privacy and security measures need refinement to protect patients appropriately.